Edukasi Pelatihan Pemasaran Online Untuk Meningkatkan Penjualan Toko Sabila Bengkulu - Hidayah, Nenden Restu; Pratiwi, Elisabeth Sekar Ambar; Jayanti, Titin Dwi; Hasibuan, Tania (Jurnal Dehasen Mengabdi, 2022)
Sabila shop is one of the centers for souvenirs typical of Bengkulu which has become various kinds of souvenirs typical of Bengkulu. The souvenirs are in the form of several types of food, drinks, clothes, batik cloth, bags and handicrafts. This shop was founded in 2014 on Jalan Anggut Atas, Ratu Samban sub-district, Bengkulu City. This store is experiencing problems in product marketing. The purpose of this research is to build a product marketing system through social media to increase sales. In building a product marketing system using several social media applications. The results of this study are to create a sabila shop to create sales applications on social media to facilitate sales and find out stock quickly.